Inflation, impôts sur le revenu et revenu réel disponible - Lizee, Ruth (L'Actualité économique, 1974)
AbstractThe purpose of this text is to examine how federal and Quebec provincial income tax policies have affected real disposable income of taxpayers in the context of the rapid inflation of the last five years. It finds that the net effect of federal fiscal reform since 1970 has been to make the tax structure more progressive. Low-income taxpayers have benefitted from lower tax rates in real terms but real tax rates have risen for those with incomes above approximately $14,000. On the provincial level, on the other hand, there has been virtually no change in the tax structure except for an increase in the threshold level below which no tax is paid. All, except the very poorest taxpayers (single persons earning less than $2,578 in 1970 or $3,200 in 1974 and married couples with two children earning less than $5,200 in 1970 or $6,300 in 1974), have paid higher taxes in real terms every year from 1970 to 1974. This is true even when provincial family allowances (which the province considers as a tax credit and as a substitute for personal exemptions for children under 16) are deducted from provincial income tax.The net result of federal and provincial tax policies, family allowance payments and deductions for various social security programs is as follows: real disposable income increased for single persons earning less than $4,000 in 1970 ($5,000 in 1974) and for two-children families earning less than $8,000 ($10,000 in 1974); it stayed about the same for single persons earning between $4,000 and $6,000 ($5,000 to $7,500 in 1974) and families earning $8,000 to $10,000 ($10,000 to $12,500 in 1974) in 1970; it fell for those with higher levels of income.